Randomized Controlled Trial Comparing Lactoferrin Plus Iron to Iron Alone for Iron Deficiency Anemia in CKD - Smita Divyaveer; Kushal Kekan; Madhuri Kashyap; Maninder Kaur; Kanchan Prajapati; Madhumita Premkumar; Deepy Zohmangaihi; Nabhajit Mallik; Deepesh Lad; Ravjit Singh Jassal; Akanksha Sharma; Simran Behl; et al. (Clinical Journal of the American Society of Nephrology, 2026)
Background: Lactoferrin, a multifunctional iron-binding glycoprotein with anti-inflammatory properties is reported to be effective in anemia in pregnant women and patients with malignancy but has not been tested elaborately in CKD. Methods: In this randomized, open-label trial, 185 patients (intention to treat) with iron-deficiency anemia (hemoglobin less than 10 g/dL, transferrin saturation less than 20%) were enrolled: 90 with CKD not on dialysis (CKD-ND) and 95 with dialysis-dependent CKD (CKD-5D). Patients were randomized to receive either oral iron (30 mg/day liposomal iron) or oral iron plus lactoferrin (100 mg twice daily) for 3 months. The primary outcome was change in hemoglobin. Secondary outcomes included iron indices and inflammatory markers (CRP, IL-6, ESR, hepcidin). Results: In the intention-to-treat analysis, lactoferrin plus iron resulted in significantly greater improvements in hemoglobin and iron parameters than iron alone in both CKD-ND and CKD-5D patients. Mean hemoglobin increased by 1.95±1.19 versus 1.33±0.86 g/dL in CKD-ND and by 1.73±0.96 versus 1.11±0.93 g/dL in CKD-5D patients receiving lactoferrin plus iron and iron alone, respectively. Improvements in iron indices were also greater with addon lactoferrin treatment. Mean difference in hepcidin levels were -20.24±15.99 vs -16.03±40.65 ng/dL in CKD-ND and -15.29±8.73 vs -20.99±20.16 ng/dL in CKD-5D patients treated with lactoferrin plus iron and iron alone respectively. Conclusion: Among patients with CKD-associated anemia, adjunctive lactoferrin therapy improved hemoglobin and iron parameters compared with oral iron alone in both non–dialysis-dependent and dialysis-dependent patients. Lactoferrin was also associated with modest improvements in inflammatory status, although effects on individual inflammatory markers were inconsistent. These findings suggest that lactoferrin may be a useful adjunct to oral iron therapy for the management of anemia in CKD especially in resource limited settings.